A spectroscopic study of substituted anthranilic acids as sensitive environmental probes for detecting cancer cells. Issue 5 (1st March 2016) - Culf, Adrian S.; Yin, Huimin; Monro, Susan; Ghosh, Anirban; Barnett, David A.; Ouellette, Rodney J.; Čuperlović-Culf, Miroslava; McFarland, Sherri A.
Graphical abstract: Abstract: Small-molecule fluorescent reporters of disease states are highly sought after, yet they remain elusive. Anthranilic acids are extremely sensitive environmental probes, and hold promise as general but selective agents for cancer-cell detection if they can be equipped with the appropriate targeting groups. The optical properties of a small library of N -isopropyl invariant anthranilic acids were investigated in methanol and chloroform. Points of variation included: fluoro, trifluoromethyl, or cyano substitution on the aromatic ring, and derivitization of the parent carboxylic acid as esters or secondary carboxamides. Phenylboronic acid conjugation at the carboxylic acid alongside un-, mono-, and dimethylated 2-amino groups was also explored. The boron-containing anthranilic acids were also evaluated as sensitive fluorescent probes for cancer cells using laser scanning confocal microscopy. In general, the compounds produced blue fluorescence that was strongly influenced by substitution and environment. 4-Trifluoromethyl and 4-cyano esters proved to be the most sensitive environmental probes with quantum yields as large as 100% in chloroform, and enhancements of up to 30-fold on going from methanol to chloroform. Stokes shifts ranged from 63 to 120 nm, generally increasing with ortho -substitution and environmental polarity. It was demonstrated that phenylboronic acid conjugation was an attractive method for cancer cell detection via boronate ester formation with overexpressed glycoproteins (with no interference from normal, healthy cells), presumably due to favorable boron-sialic acid interactions.